Moral Formation Efforts at Al-Bayyinah Islamic School Through Da’wa and Character Education - Febrianti, Erlyana; Rahmat, Munawar; Suresman, Edi; Baldan Haramain, Fathur (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to explore the role of da'wah and character education in shaping morals at Al Bayyinah Islamic Boarding School. The research methodology used is a qualitative approach with a case study. This study uses primary and secondary data. Primary data were obtained through interviews with the principal, teachers, parents, and students, as well as through direct observation and documentation related to the learning process. Meanwhile, secondary data includes journals relevant to the topic of this study, where data is collected through in-depth interviews, observations, and document analysis. Data analysis techniques used include data reduction, data presentation, and drawing conclusions using a thematic analysis approach to identify patterns and relationships between data. The subjects in this study were the Principal of Al-Bayyinah Islamic Boarding School, the Supervisor/Guardian, the Deputy Head of Curriculum, the Akidah Akhlak Teacher, and Al-Bayyinah Students. The results of the study indicate that the integration between da'wah and character education at Al Bayyinah Islamic Boarding School is carried out through a structured curriculum, extracurricular programs, and routine religious activities. Teaching Islamic values such as honesty, responsibility, and tolerance, as well as the habituation of positive behavior in daily life at school, has proven effective in shaping noble morals in students. In conclusion, preaching and character education that are applied consistently and systematically can produce students who have noble morals and behave well in accordance with the Islamic values that are taught.